Evaluation of Tropical Rainfall Measuring Mission, Integrated Multi‐satellite Retrievals for GPM, Climate Hazards Centre InfraRed Precipitation with Station data, and European Centre for Medium‐Range Weather Forecasts Reanalysis v5 data in estimating precipitation and capturing meteorological droughts over Iran. (1st September 2021) - Keikhosravi‐Kiany, Mohammad Sadegh; Masoodian, Seyed Abolfazl; Balling, Robert C.; Darand, Mohammad
Abstract: Satellite remote‐sensing products with high spatial and temporal resolution are viable sources of precipitation information, especially for data‐sparse and remote regions. The aim of this study is to examine the performance of four precipitation products including Integrated Multi‐satellite Retrievals for GPM (GPM IMERG), Tropical Rainfall Measuring Mission (TRMM 3B43), Climate Hazards Centre InfraRed Precipitation with Station data (CHIRPS), and European Centre for Medium‐Range Weather Forecasts Reanalysis v5 (ERA5) in estimating precipitation and capturing meteorological droughts over Iran for the time span from 2001 to 2019. For this aim, a ground‐based gridded precipitation dataset was constructed over the country using a dense network of quality‐controlled rain gauges as a reference dataset. Different statistical metrics including the correlation coefficient (CC), the bias, the relative bias, and the root mean square error (RMSE) were applied to evaluate the performance of the products. The results suggest that GPM IMERG and TRMM 3B43 outperform CHIRPS and ERA5 in capturing the spatial distribution of precipitation and meteorological drought events across the country. The estimates of precipitation from the four products are seasonally influenced, with the least accurate precipitation estimates during summer season over the southern shores of the Caspian Sea. The GPM IMERG and TRMM 3B43, with higher CC and lower RMSE, show better performance in detecting drought events at both short and long time scales while the CHIRPS demonstrates the least accuracy. Spatially, all of the products show the best performance in identifying drought events over western and southwestern regions. Abstract : Performance of four precipitation products including Integrated Multi‐satellite Retrievals for GPM (GPM IMERG), Tropical Rainfall Measuring Mission, Climate Hazards Centre InfraRed Precipitation with Station data, and European Centre for Medium‐Range Weather Forecasts Reanalysis v5 were evaluated against a ground‐based gridded precipitation (NGPD) dataset in estimating precipitation and capturing meteorological droughts in Iran over 2001–2019. The GPM IMERG data with higher correlation coefficients and lower root mean square errors show the best performance in detecting drought events at both short and long time scales. Spatially, the four precipitation products show the best performance in identifying drought events over western and southwestern regions of Iran.